2011
DOI: 10.1007/s12026-011-8259-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells essential to prevent the loss of self-tolerance in murine models of erythrocyte-specific autoantibody responses

Abstract: The spontaneous appearance of anti-erythrocyte autoantibodies resulting in autoimmune hemolytic anemia described in NZB mice more than 40 years ago provided a model for the study of mechanisms behind the loss of self-tolerance. We developed an in vitro model of this anti-MRBC response in which CD8(+) suppressor T cells were shown to be a controlling element. CD8(+) T cells from young NZB mice co-cultured with spleen cells from old, actively autoimmune NZB mice suppressed the anti-MRBC responses of the old mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…+ T cells from young NZB mice were co-cultured with splenic cells from old, actively autoimmune NZB mice indicated that these CD8 + T cells were capable of suppressing autoantibody responses, evidence that they may also have a role in regulating disease [11]. While identification of the T cell subset(s) that mediate and transmit tolerogenic responses in AIHA continues, it is also important to address, at a molecular level, mechanisms that underpin this important immunological feature.…”
Section: Cd25mentioning
confidence: 99%
See 1 more Smart Citation
“…+ T cells from young NZB mice were co-cultured with splenic cells from old, actively autoimmune NZB mice indicated that these CD8 + T cells were capable of suppressing autoantibody responses, evidence that they may also have a role in regulating disease [11]. While identification of the T cell subset(s) that mediate and transmit tolerogenic responses in AIHA continues, it is also important to address, at a molecular level, mechanisms that underpin this important immunological feature.…”
Section: Cd25mentioning
confidence: 99%
“…In this model system, the mechanism by which splenic lymphocytes 'transfer' tolerance to the recipients remains unknown, although a role for CD4 + CD25 + regulatory T cells has been suggested [10]. Further, analysis of in-vitro assays where CD8 + T cells from young NZB mice were co-cultured with splenic cells from old, actively autoimmune NZB mice indicated that these CD8 + T cells were capable of suppressing autoantibody responses, evidence that they may also have a role in regulating disease [11]. While identification of the T cell subset(s) that mediate and transmit tolerogenic responses in AIHA continues, it is also important to address, at a molecular level, mechanisms that underpin this important immunological feature.…”
Section: Introductionmentioning
confidence: 99%